2020
DOI: 10.3390/en13040956
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting by a Novel Substitution for Expansion Valves: Special Focus on City Gate Stations of High-Pressure Natural Gas Pipelines

Abstract: A countless amount of energy has been wasted in all kinds of expansion valves (EV) in industries. In fact, EVs, including regulators, throttling valves, capillary tubes, etc., have been used to intentionally reduce the potential of carrier fluid. City gate stations (CGS) have been recognized as one of the important points with high potential for energy harvesting due to its function for regulating natural gas (NG) pressure by EV. In this study, Tesla turbine (TT) is introduced as a new candidate for substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In recent years, with regard to the development of typical renewable energy low-temperature resources and a large number of waste heat resources generated by industrial processes or prime movers, the organic Rankine cycle power system (ORC) has been in a leading position with its good thermodynamic characteristics and high flexibility. The Tesla turbine, as a new expander for small and micro power applications, has attracted more and more attention in the scientific community because of its low cost and high reliability [19,[55][56][57][58][59]. It is a bladeless turbine composed of one or more nozzles that inject the working fluid tangentially into the rotor.…”
Section: Second-generation Disc Pumpmentioning
confidence: 99%
“…In recent years, with regard to the development of typical renewable energy low-temperature resources and a large number of waste heat resources generated by industrial processes or prime movers, the organic Rankine cycle power system (ORC) has been in a leading position with its good thermodynamic characteristics and high flexibility. The Tesla turbine, as a new expander for small and micro power applications, has attracted more and more attention in the scientific community because of its low cost and high reliability [19,[55][56][57][58][59]. It is a bladeless turbine composed of one or more nozzles that inject the working fluid tangentially into the rotor.…”
Section: Second-generation Disc Pumpmentioning
confidence: 99%
“…In the last year, a few research papers have been published, reporting the development of an innovative test rig for the characterization of the flow within a 2phase Tesla turbine [16], the possible benefits of utilizing a Tesla turbine instead of an expansion valve within a high-efficiency HVAC system [17], or for the energy harvesting when replacing the expansion valves in high-pressure natural gas pipelines [18,19].…”
Section: Tesla Turbinementioning
confidence: 99%
“…[7][8] There are several studies on recovering physical exergy of high pressure natural gas during pressure reduction pro-cess most of them focus on the pressure exergy recovering devices such as turboexpander. [9][10][11] Researchers have developed case studies to estimate the amount of exergy recovery and the economics of turboexpander installations in NG pressure reduction stations. It was found that thermal efficiency of system increase about 8% in the optimum state [12][13][14] some researchers developed a mathematical model to predict the performance of a twin-screw expander as power generation unit.…”
Section: Introductionmentioning
confidence: 99%